2016
DOI: 10.1016/j.biortech.2015.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Laccase–syringaldehyde-mediated degradation of trace organic contaminants in an enzymatic membrane reactor: Removal efficiency and effluent toxicity

Abstract: Redox-mediators such as syringaldehyde (SA) can improve laccase-catalyzed degradation of trace organic contaminants (TrOCs) but may increase effluent toxicity. The degradation performance of 14 phenolic and 17 non-phenolic TrOCs by a continuous flow enzymatic membrane reactor (EMR) at different TrOC and SA loadings was assessed. A specific emphasis was placed on the investigation of the toxicity of the enzyme (laccase), SA, TrOCs and the treated effluent. Batch tests demonstrated significant individual and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 30 publications
4
45
1
Order By: Relevance
“…Laccases have the ability to oxidize a wide range of aromatic and non-aromatic compounds which includes substituted phenols, some inorganic ions, and variety of non-phenolic compounds (Matera et al 2008;Songulashvili et al 2016;Nguyen et al 2016;Surwase et al 2016). Due to its low substrate specificity, it can act on a broad range of substrates and has attracted considerable attention in different environmental, industrial, and biotechnological sectors (Afreen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Laccases have the ability to oxidize a wide range of aromatic and non-aromatic compounds which includes substituted phenols, some inorganic ions, and variety of non-phenolic compounds (Matera et al 2008;Songulashvili et al 2016;Nguyen et al 2016;Surwase et al 2016). Due to its low substrate specificity, it can act on a broad range of substrates and has attracted considerable attention in different environmental, industrial, and biotechnological sectors (Afreen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An overall degradation of only 40-65% was achieved by the MD-EMBR for a number of non-phenolic TrOCs (Figure 2), however, these removal efficiencies in fact compare favorably with those reported in the literature [12,15,37]. For instance, laccase catalyzed degradation of carbamazepine, clofibric acid, fenoprop and atrazine has been reported to be less than 10% in both batch and continuous flow ultrafiltration based enzymatic bioreactors [15,18,40].…”
Section: Troc Degradation In Enzymatic Bioreactormentioning
confidence: 53%
“…Indeed Margot et al [12] observed that degradation of diclofenac by laccase was significantly higher in the mixture of TrOCs containing diclofenac, bisphenol A and mefenamic acid than its degradation as a single compound. It is possible that complete retention of phenoxyl radicals formed due to the degradation of phenolic TrOCs aided better degradation of non-phenolic TrOCs by MD-EMBR as compared to previously developed UF-EMBR [18,37]. Further investigation would be required to substantiate this hypothesis but that is beyond the scope of this study.…”
Section: Troc Degradation In Enzymatic Bioreactormentioning
confidence: 63%
See 2 more Smart Citations